PERBEDAAN MANAJEMEN LABA AKRUAL DAN MANAJEMEN LABA RILL SEBELUM DAN SESUDAH ADOPSI IFRS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Fitri Asni; Mega Mayasari (Pusat P2M Politeknik Negeri Batam, 2018)
The purpose of this research is to examine and provide empirical evidence regarding the presence of management differences actual benefit before and after IFRS adopstion which is measured by using jones models modification and the differences of management real benefit through the expense of production. The adopstion of IFRS which is done by many countries be able to increase the benefit of quality management and the punctuality of accountancy information.Samples of this research are 78 manufactur campanies which are listed in BEI since 2010-2011 dan 2013-2014 which 293 data. The result of this research indicates that there is not differences between the benefit of accrual management before and after IFRS adoption , but there is differentiation of real benefit management before and after IFRS adopstion.